Implementasi Digital Marketing pada “UMKM HerJamu” - Pratama Herman, Fadiya; Arvika Sari, Rini (Politeknik Kampar, 2025)
This Community Service project aims to implement a digital marketing strategy for UMKM HerJamu in Desa Pangkalan Jambi, Bengkalis, to expand market reach and increase sales of traditional herbal drinks made from natural spices. The methods used include SWOT analysis, the marketing mix (4P), and the STP approach (Segmenting, Targeting, Positioning). The strategies implemented include creating a Google My Business account, selecting social media platforms such as Instagram and Facebook, preparing a content calendar, and publishing promotional content over the course of one month. The results of this implementation show an increase in audience engagement, brand awareness, and consumer interest from outside the region. Consistent and informative content strategies have proven effective in building trust and expanding the market. Despite challenges such as limited human resources (HR) and low digital literacy, these were overcome through training and mentoring. This Community Service project supports the digital transformation of HerJamu and provides practical guidance for other SMEs to leverage digital marketing as a strategy for business development, while contributing to the government's program to promote the digitalization of SMEs in Indonesia.